KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MTS PADA MATERI ALJABAR - Alfina, Siti; Sutirna, Sutirna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Students who tend to only follow directions from the teacher cause learning to be meaningless. This meaningless learning causes students to be unable to master mathematical concepts and principles, so that when given a problem students are unable to work on the problem independently. Therefore, this study aims to describe the mathematical understanding ability of MTs students on algebraic material using descriptive qualitative. The research subjects used were 6 students who were taken using purposive sampling technique. The test instrument is in the form of a description of algebraic material consisting of 7 questions that are adjusted to the indicators of mathematical understanding ability according to the Ministry of National Education and non-test in the form of interviews. The data analysis technique used in this research is data collection, data reduction, data presentation, and drawing conclusions. The results of the student's instrument will be analyzed based on indicators of mathematical understanding ability by converting the score into percentage form. The results obtained from 7 indicators of mathematical understanding, 5 of which are already above 50% and 2 others are still below 50%. These results indicate that students' mathematical understanding abilities are still not optimal because students still have difficulty applying their understanding in solving algebraic questions, especially on indicators of building necessary conditions and applying concepts or algorithms in problem solving.